Correction to: Using non‑invasive behavioral and physiological data to measure biological age in wild baboons - Chelsea J. Weibel; Mauna R. Dasari; David A. Jansen; Laurence R. Gesquiere; Raphael S. Mututua; J. Kinyua Warutere; Long’ida I. Siodi; Susan C. Alberts; Jenny Tung; Elizabeth A. Archie (GeroScience, 2024)

Using non-invasive behavioral and physiological data to measure biological age in wild baboons - Chelsea J. Weibel; Mauna R. Dasari; David A. Jansen; Laurence R. Gesquiere; Raphael S. Mututua; J. Kinyua Warutere; Long’ida I. Siodi; Susan C. Alberts; Jenny Tung; Elizabeth A. Archie (GeroScience, 2024)
Biological aging is near-ubiquitous in the animal kingdom, but its timing and pace vary between individuals and over lifespans. Prospective, individual-based studies of wild animals—especially non-human primates—help identify the social and environmental drivers of this variation by indicating the conditions and exposure windows that affect aging processes. However, measuring individual biological age in wild primates is challenging because several of the most promising methods require invasive sampling. Here, we leverage observational data on behavior and physiology, collected non-invasively from 319 wild female baboons across 2402 female-years of study, to develop a composite predictor of age: the non-invasive physiology and behavior (NPB) clock. We found that age predictions from the NPB clock explained 51% of the variation in females’ known ages. Further, deviations from the clock’s age predictions predicted female survival: females predicted to be older than their known ages had higher adult mortality. Finally, females who experienced harsh early-life conditions were predicted to be about 6 months older than those who grew up in more benign conditions. While the relationship between early adversity and NPB age is noisy, this estimate translates to a predicted 2–3 year reduction in mean adult lifespan in our model. A constraint of our clock is that it is tailored to data collection approaches implemented in our study population. However, many of the clock’s components have analogs in other populations, suggesting that non-invasive data can provide broadly applicable insight into heterogeneity in biological age in natural populations.

Multi-scale predictors of parasite risk in wild male savanna baboons (Papio cynocephalus) - Bobby Habig; David A. W. A. M. Jansen; Mercy Y. Akinyi; Laurence R. Gesquiere; Susan C. Alberts; Elizabeth A. Archie (Behavioral Ecology and Sociobiology, 2019)

Development, diet and dynamism: longitudinal and cross‐sectional predictors of gut microbial communities in wild baboons - Tiantian Ren; Laura E. Grieneisen; Susan C. Alberts; Elizabeth A. Archie; Martin Wu (Environmental Microbiology, 2016)
Summary Gut bacterial communities play essential roles in host biology, but to date we lack information on the forces that shape gut microbiota between hosts and over time in natural populations. Understanding these forces in wild primates provides a valuable comparative context that enriches scientific perspectives on human gut microbiota. To this end, we tested predictors of gut microbial composition in a well‐studied population of wild baboons. Using cross‐sectional and longitudinal samples collected over 13 years, we found that baboons harbour gut microbiota typical of other omnivorous primates, albeit with an especially high abundance of Bifidobacterium . Similar to previous work in humans and other primates, we found strong effects of both developmental transitions and diet on gut microbial composition. Strikingly, baboon gut microbiota appeared to be highly dynamic such that samples collected from the same individual only a few days apart were as different from each other as samples collected over 10 years apart. Despite the dynamic nature of baboon gut microbiota, we identified a set of core taxa that is common among primates, supporting the hypothesis that microbiota codiversify with their host species. Our analysis identified two tentative enterotypes in adult baboons that differ from those of humans and chimpanzees.

Costs of reproduction in a long-lived female primate: injury risk and wound healing - Elizabeth A. Archie; Jeanne Altmann; Susan C. Alberts (Behavioral Ecology and Sociobiology, 2014)

Elephant behaviour and conservation: social relationships, the effects of poaching, and genetic tools for management - ELIZABETH A. ARCHIE; PATRICK I. CHIYO (Molecular Ecology, 2012)
Genetic tools are increasingly valuable for understanding the behaviour, evolution, and conservation of social species. In African elephants, for instance, genetic data provide basic information on the population genetic causes and consequences of social behaviour, and how human activities alter elephants’ social and genetic structures. As such, African elephants provide a useful case study to understand the relationships between social behaviour and population genetic structure in a conservation framework. Here, we review three areas where genetic methods have made important contributions to elephant behavioural ecology and conservation: (1) understanding kin‐based relationships in females and the effects of poaching on the adaptive value of elephant relationships, (2) understanding patterns of paternity in elephants and how poaching can alter these patterns, and (3) conservation genetic tools to census elusive populations, track ivory, and understand the behavioural ecology of crop‐raiding. By comparing studies from populations that have experienced a range of poaching intensities, we find that human activities have a large effect on elephant behaviour and genetic structure. Poaching disrupts kin‐based association patterns, decreases the quality of elephant social relationships, and increases male reproductive skew, with important consequences for population health and the maintenance of genetic diversity. In addition, we find that genetic tools to census populations or gather forensic information are almost always more accurate than non‐genetic alternatives. These results contribute to a growing understanding of poaching on animal behaviour, and how genetic tools can be used to understand and conserve social species.

Major histocompatibility complex variation and evolution at a single, expressed DQA locus in two genera of elephants - Elizabeth A. Archie; Tammy Henry; Jesus E. Maldonado; Cynthia J. Moss; Joyce H. Poole; Virginia R. Pearson; Suzan Murray; Susan C. Alberts; Robert C. Fleischer (Immunogenetics, 2010)

Fine‐scale population genetic structure in a fission–fusion society - ELIZABETH A. ARCHIE; JÉSUS E. MALDONADO; JULIE A. HOLLISTER‐SMITH; JOYCE H. POOLE; CYNTHIA J. MOSS; ROBERT C. FLEISCHER; SUSAN C. ALBERTS (Molecular Ecology, 2008)
Nonrandom patterns of mating and dispersal create fine‐scale genetic structure in natural populations — especially of social mammals — with important evolutionary and conservation genetic consequences. Such structure is well‐characterized for typical mammalian societies; that is, societies where social group composition is stable, dispersal is male‐biased, and males form permanent breeding associations in just one or a few social groups over the course of their lives. However, genetic structure is not well understood for social mammals that differ from this pattern, including elephants. In elephant societies, social groups fission and fuse, and males never form permanent breeding associations with female groups. Here, we combine 33 years of behavioural observations with genetic information for 545 African elephants ( Loxodonta africana ), to investigate how mating and dispersal behaviours structure genetic variation between social groups and across age classes. We found that, like most social mammals, female matrilocality in elephants creates co‐ancestry within core social groups and significant genetic differentiation between groups (Φ ST = 0.058). However, unlike typical social mammals, male elephants do not bias reproduction towards a limited subset of social groups, and instead breed randomly across the population. As a result, reproductively dominant males mediate gene flow between core groups, which creates cohorts of similar‐aged paternal relatives across the population. Because poaching tends to eliminate the oldest elephants from populations, illegal hunting and poaching are likely to erode fine‐scale genetic structure. We discuss our results and their evolutionary and conservation genetic implications in the context of other social mammals.

Behavioural inbreeding avoidance in wild African elephants - ELIZABETH A. ARCHIE; JULIE A. HOLLISTER‐SMITH; JOYCE H. POOLE; PHYLLIS C. LEE; CYNTHIA J. MOSS; JÉSUS E. MALDONADO; ROBERT C. FLEISCHER; SUSAN C. ALBERTS (Molecular Ecology, 2007)
The costs of inbreeding depression, as well as the opportunity costs of inbreeding avoidance, determine whether and which mechanisms of inbreeding avoidance evolve. In African elephants, sex‐biased dispersal does not lead to the complete separation of male and female relatives, and so individuals may experience selection to recognize kin and avoid inbreeding. However, because estrous females are rare and male–male competition for mates is intense, the opportunity costs of inbreeding avoidance may be high, particularly for males. Here we combine 28 years of behavioural and demographic data on wild elephants with genotypes from 545 adult females, adult males, and calves in Amboseli National Park, Kenya, to test the hypothesis that elephants engage in sexual behaviour and reproduction with relatives less often than expected by chance. We found support for this hypothesis: males engaged in proportionally fewer sexual behaviours and sired proportionally fewer offspring with females that were natal family members or close genetic relatives (both maternal and paternal) than they did with nonkin. We discuss the relevance of these results for understanding the evolution of inbreeding avoidance and for elephant conservation.